Spinal Direct Current Stimulation (tsDCS) in Hereditary Spastic Paraplegias (HSP): A sham-controlled crossover study. Issue 1 (January 2019) - Bocci, T.; Ardolino, G.; Nigro, M.; Vergari, M.; Di Fonzo, A.; Bonato, S.; Cogiamanian, F.; Sartucci, F.; Barbieri, S.; Priori, A.
Abstract : Hereditary spastic paraplegia (HSP) comprises a heterogeneous group of neurodegenerative diseases characterized by progressive spasticity and lower limb weakness. We assessed the effects of transcutaneous spinal direct current stimulation (tsDCS) in HSP. Motor evoked potentials, H-reflex, Patellar tendon reflex (T-reflex), F-waves, the Ashworth scale for clinical spasticity, the 5'-walking test and the Spastic Paraplegia rating scale were assessed. tsDCS (anodal or sham, 2.0 mA, 20 min, 5 consecutive days) was delivered over the lower thoracic spinal cord (T10-T12). Patients were evaluated before tsDCS (T0), immediately at the end of the stimulation (T1), and one week (T2), one month (T3) and two months (T4) after tsDCS. Whereas T-reflex area increased after sham intervention, it was unchanged after anodal tsDCS (p = 0.0088). T-reflex latency also was modulated by the two different polarities (T2: p = 0.0139). A significant improvement in the Ashworth scores was observed in the anodal group at T1 (p = 0.0137) and T4 (p = 0.0244), but not in the 5′-walking test and SPRS. Anodal tsDCS prevented the progressive increase of spinal cord excitability that naturally occurred during disease progression. tsDCS might be a complementary strategy for the treatment of spasticity in HSP.